Unveiling inequality: the sociological dynamics of road infrastructure development and social justice in rural Eastern Cape, South Africa - Siyabulela Christopher Fobosi; Thelma Malima (Frontiers in Sociology)
This paper examines the systemic and multidimensional impacts of inadequate road infrastructure on social inequality in the rural Eastern Cape province of South Africa, focusing on the Hlankomo community from Mdeni to Upper Tsitsana. By integrating a sociological framework, the study explores how deteriorating road conditions perpetuate structural and symbolic violence, exacerbating economic marginalization, social exclusion, and cultural disempowerment. Drawing on site observations, qualitative interviews, and photographic evidence, the research highlights how poor road infrastructure restricts access to essential services, including healthcare, education, and economic opportunities, deepening historical and spatial inequalities. The findings underscore the urgent need for transformative, equity-driven infrastructure policies that address governance inefficiencies, historical neglect, and systemic marginalization. By prioritizing inclusivity, social justice, and sustainable development, this paper contributes to the broader discourse on rural development and infrastructural justice in South Africa’s marginalized landscapes.